Recent advances in methanation catalysts for the production of synthetic natural gas. Issue 29 (2nd April 2015) - Gao, Jiajian; Liu, Qing; Gu, Fangna; Liu, Bin; Zhong, Ziyi; Su, Fabing
<x xml:space="preserve">Abstract</x> This review summarizes the recent progress in methanation catalysts for SNG production, which will provide insights for future catalysts design.